Comparison of different surgical techniques for chronic subdural hematoma: a network meta-analysis - Qiu, Youjia; Xie, Minjia; Duan, Aojie; Yin, Ziqian; Wang, Menghan; Chen, Xi; Chen, Zhouqing; Gao, Wei; Wang, Zhong (Frontiers in Neurology, 2023)
Background Chronic subdural hematoma (CSDH) is a neurosurgical condition with high prevalence. Many surgical approaches are recommended for treating CSDH, but there needs to be a consensus on the optimal technique. This network meta-analysis (NMA) compared the efficacy and safety of different surgical treatments for CSDH. Methods Electronic databases, including PubMed, Embase, and the Cochrane Library, were searched for relevant studies up to February 2023. An NMA was performed to compare the outcomes of patients with CSDH treated by single-hole or double-hole craniotomy (SBHC and DBHC, respectively), twist-drill craniotomy (TDC), mini-craniotomy, and craniotomy. The NMA protocol was registered at INPLASY (registration no. 202320114). Results The NMA included 38 studies with 7,337 patients. For efficacy outcomes, DBHC showed the highest surface under the cumulative ranking area (SUCRA) values for recurrence (96.3%) and reoperation (87.4%) rates. DBHC differed significantly from mini-craniotomy in recurrence rate (odds ratio [OR] = 0.58, 95% confidence interval [CI]: 0.35, 0.97) and from SBHC (OR = 0.48, 95% CI: 0.25, 0.91) and TDC (OR = 0.40, 95% CI: 0.20, 0.82) in reoperation rate. For operative time, TDC was superior to SBHC (mean difference [MD] = −2.32, 95% CI: −3.78 to −0.86), DBHC (MD = −3.61, 95% CI: −5.55, −1.67), and mini-craniotomy (MD = −3.39, 95% CI: −5.70, −1.08). Patients treated by TDC had a shorter hospital stay than those treated by SBHC (MD = −0.82, 95% CI: −1.51, −0.12). For safety outcomes, there were no significant differences between groups in mortality and complication rates; however, mini-craniotomy (79.8%) and TDC (78.1%) had the highest SUCRAs. Conclusion DBHC may be the most effective surgical treatment for CSDH based on the low recurrence and reoperation rates, although all examined techniques were relatively safe. Systematic review registration https://inplasy.com/inplasy-2023-2-0114/